Persistent COVID and a return to sport - Giusto, E.; Asplund, C. A. (Current Sports Medicine Reports, 2022)
Coronavirus disease (COVID) has become a global pandemic that has widely impacted athletes at all levels of competition. For many athletes infected with COVID, the course is mild or asymptomatic, and most athletes are able to return to play in a matter of weeks. However, 10% to 15% of people infected with COVID will go on to have prolonged COVID symptoms that last for weeks to months and impact their ability to function and exercise. Not much is known about why certain people become "COVID long-haulers," nor are there any predictive tools to predetermine who may have prolonged symptoms. However, many athletes will suffer from prolonged symptoms that may require further evaluation and may prolong their return to exercise, training, and competition. The purpose of this article is to discuss a framework in which sports medicine and primary care physicians can use to evaluate COVID long-haulers and help them return to sport.